Free broadcast DGPS service in marine: how good is it? - Che Hassan, Rozaimi (2005)
Differential GPS (DGPS) has been used widely in many types of application including for marine navigation and hydrographic surveying. Most of the recent DGPS receiver development applies the use of code and carrier phase on single frequency L1 C/A code receiver for submetre horizontal accuracy. Differential Global Navigation Satellite System (DGNSS) radio beacon is a system that uses the concept of DGPS based on pseudorange measurements. This system provides free DGPS corrections using the commercial reference station with proper receivers. The availability of reference station that operates 24 hours a day means that the users are no longer required to set up their own reference station. This study is intended to evaluate the performance of DGNSS radio beacon, not only for horizontal positioning but also for data availability and reliability at the remote receiver. For this purpose, static and dynamic test have been carried out on the DGPS corrections received from DGNSS radio beacon. Both of the tests make use of the National Marine Electronic Associations 0183 (NMEA 0183) data format generate by remote receiver to examine the DGPS broadcast signal. The results show how the distance separation (static test) effects the age of DGPS correction, horizontal dilution of precision (HDOP), numbers of satellite use and also the signal strength recorded at remote receiver. Meanwhile, the tracking method (dynamic test) differentiates the automatic and manual tracking results. This is to estimate the most suitable method to be used for marine navigation and hydrographic surveys.